Enslaved Ecopoetics: - Shaibal Dev Roy (Crossings, 2022)
Scholars, such as Kimberly Ruffin and Katherine Lynes, reconsider American environmental poetry that excludes African American ecopoetic traditions of the antebellum period. According to Ruffin, in order to reconstruct and enhance our sense of ecopoetry, we must reevaluate the black tradition of nature poetry, exemplifying the contemporary approaches to slavery in the USA and elsewhere. Likewise, Lyne’s “reclamation ecopoetics” attends to the history of dangers, despite centuries of methodical and organized exploitation, that human groups bring to the black human subjects as well as to non-human nature. Building on this scholarship, I focus on the nature poems of George Moses Horton (1797- 1883), the life-long enslaved poet, that highlight the inseparable unity of nature and humans. Horton’s poetry deployed nature to prove both the humanity and the intellectuality of the enslaved. My study traces a history of American enslaved ecopoetics that requires us to think of the enslaved human subjects as individuals whose nature poetry hinges on the dangers of subjection and exploitation of chattel slavery. My essay resituates Horton, the black bard of North Carolina, in the nineteenth-century American paradigm, analyzing his poetry and his racial subjugation from an ecocritical perspective.